The giver ebook - Lowry, Lois (The Giver Quartet, 1993)
In Lois Lowry's Newbery Medal–winning classic, twelve-year-old Jonas lives in a seemingly ideal world. Not until he is given his life assignment as the Receiver does he begin to understand the dark secrets behind his fragile community. Life in the community where Jonas lives is idyllic. Designated birthmothers produce newchildren, who are assigned to appropriate family units. Citizens are assigned their partners and their jobs. No one thinks to ask questions. Everyone obeys. Everyone is the same. Except Jonas. Not until he is given his life assignment as the Receiver of Memory does he begin to understand the dark, complex secrets behind his fragile community. Gradually Jonas learns that power lies in feelings. But when his own power is put to the test—when he must try to save someone he loves—he may not be ready. Is it too soon? Or too late? Told with deceptive simplicity, this is the provocative story of a boy who experiences something incredible and undertakes something impossible. In the telling it questions every value we have taken for granted and reexamines our most deeply held beliefs. The Giver has become one of the most influential novels of our time. Don't miss the powerful companion novels in Lois Lowry's Giver Quartet: Gathering Blue, Messenger, and Son.